Privacy and data protection towards elderly healthcare - Costa, Ângelo (2013)
Developed societies are registering a dramatic change in terms of population evolution, being the most important fact the high tendency in the ageing of the whole population. An alarming fact is that the birth-rate is dropping very fast, inverting the ageing pyramid that used to have a higher incidence on the young population, now having a higher incidence in the older population. In the quest to provide answers to some problems the elderly population has, applications and projects arise from the Ambient Assisted Living area, providing services that help the user in his daily life, providing the needed help and trying to be the less invasive as possible. The fact is that these systems operate optimally by using information about the user, assisting him accordingly to his preferences. The data gathered for such events is highly personal and sensitive. Being this data escalating several stages until it finally is ready to be inserted in the system. This can cause a loss of privacy and data protection. In this document we present an Ambient Assisted Living project towards assistance to an elderly population and the problems and possible solutions in the legal area towards loss of privacy, data protection and personal information.